The Very Fairy Princess : Valentines From The Heart - Andrews, Julie; Hamilton, Emma Walton; Davenier, Christine (New York, NY : LB kids, 2015)
"Gerry, the very fairy princess, makes beautiful valentine's day cards for her friends at school. But her cards get left behind on the big day---can Gerry find a new way to celebrate what makes her friends sparkle?"--Page [4] of cover.
First published in 2013 in hardcover by Little, Brown and Company.
"Special bonus stickers inside!"--Cover.
Keywords: Valentine's Day -- Juvenile fiction; Friendship -- Juvenile fiction; Schools -- Juvenile fiction; Princesses -- Juvenile fiction; Schools -- Fiction; Friendship; Princesses; Schools; Valentine's Day; Schools -- Fiction; Princesses -- Fiction; Valentine's Day -- fiction; Friendship -- Fiction; Valentine's Day -- Fiction; Juvenile works; Fiction